A Divergent Approach to the Marine Diterpenoids (+)‐Dictyoxetane and (+)‐Dolabellane V. Issue 42 (7th September 2016) - Hugelshofer, Cedric L.; Magauer, Thomas
Abstract: We present a full account of the development of a strategy that culminated in the first total syntheses of the unique oxetane‐containing natural product (+)‐dictyoxetane and the macrocyclic diterpene (+)‐dolabellane V. Our retrosynthetic planning was guided by both classical and nonconventional strategies to construct the oxetane, which is embedded in an unprecedented 2, 7‐dioxatricyclo[4.2.1.0 3, 8 ]nonane ring system. Highlights of the successful approach include highly diastereoselective carbonyl addition reactions to assemble the full carbon skeleton, a Grob fragmentation to construct the 11‐membered macrocycle of (+)‐dolabellane V, and a bioinspired 4‐ exo ‐tet, 5‐ exo ‐trig cyclization sequence to form the complex dioxatricyclic framework of (+)‐dictyoxetane. Furthermore, an unprecedented strain‐releasing type I dyotropic rearrangement of an epoxide‐oxetane substrate was developed. Abstract : An evolution of strategies : A full account of the first total syntheses of the unique oxetane‐containing natural product (+)‐dictyoxetane and the macrocyclic diterpene (+)‐dolabellane V is presented. Key features are a Grob fragmentation to construct the 11‐membered macrocycle of (+)‐dolabellane V and a bioinspired 4‐ exo ‐tet, 5‐ exo ‐trig cyclization sequence to form the complex dioxatricyclic framework of (+)‐dictyoxetane.